Interrogating perceived relevance and feasibility of HIV pre-exposure prophylaxis: A novel model of PrEP acceptability among cisgender women who inject drugs - Leanne Zhang; Joseph G. Rosen; Lyra Cooper; Praise F. Olatunde; Danielle Pelaez; Susan G. Sherman; Ju Nyeong Park; Jennifer L. Glick (SSM: Qualitative Research in Health, 2023)
Introduction: Uptake of daily oral HIV pre-exposure prophylaxis (PrEP) remains low among cisgender women who inject drugs (WWID) in the U.S., who experience elevated sexual- and injection-mediated HIV exposure risks. While anticipated barriers to PrEP uptake have been explored, further work is needed to situate PrEP acceptability (i.e., PrEP interest and willingness) within the context of WWID’s lives and the HIV risk environment. Methods: We conducted semi-structured, in-depth interviews (N = 27) with cisgender WWID in Baltimore, Maryland, between April–September 2021. Interviews explored women’s daily survival needs, substance use practices, healthcare experiences, HIV risk perception, and PrEP perspectives. Thematic analysis revealed complex dimensions of WWID’s health perspectives and HIV risk conceptualization, from which a Psychosocial Model of PrEP Acceptability and a novel construct of ‘perceived PrEP relevance’ were developed using a grounded theory approach. Results: In our Psychosocial Model of PrEP Acceptability, anticipated PrEP feasibility and perceived PrEP relevance shape women’s interest in and willingness to initiate PrEP. Attending to PrEP-related healthcare tasks (e.g., medical appointments, bloodwork) and managing a daily medication regimen were anticipated as feasible but would likely be de-prioritized relative to women’s competing substance-related and survival needs. Women’s perceptions of both their locus of HIV risk and sufficiency of existing HIV prevention practices determined their perceived PrEP relevance. PrEP was least relevant for women perceiving their prevention practices as sufficient to mitigate self-controlled HIV risk and most relevant for women perceiving their prevention practices as insufficient to mitigate environmentally shaped HIV risk. Conclusions: Our models demonstrate how PrEP acceptability is influenced by WWID’s lived experiences and complex risk conceptualization. Effective multilevel interventions to enhance PrEP engagement should support women’s competing needs, affirm women’s existing prevention strategies, and address the harms of the HIV risk environment.